Biofilm Forming Antibiotic Resistant Enteric Bacteria from Drinking Jar Water in Kathmandu Valley, Nepal (Tribhuvan University Journal of Microbiology, 2025)
Objectives: To determine bacteriological quality of drinking jar water from Kathmandu valley, Nepal and detect biofilm forming antibiotic resistant enteric bacteria.Methods: A cross-sectional study was conducted during February-March 2023. Drinking jar water samples (n=36) were collected from Kathmandu valley. Isolation and enumeration of coliform were done by membrane filtration method. Bacterial isolates were characterized by biotyping, antibiotic susceptibility pattern was assessed and biofilm formation was detected by tube adhesion method.Results: Bacteriological analysis revealed the contamination of 97.2% of water samples with total coliform and 11.1% of water samples with thermotolerant coliform. Among 78 bacterial isolates, Klebsiella spp. (32.1%) was the most common bacteria followed by Escherichia coli (15.4%). Most of E. coli and Klebsiella spp. isolates were resistant to antibiotics. Multiple antibiotic resistant (MAR) Klebsiella spp. and thermotolerant Klebsiella spp. were detected. Biofilm forming E. coli (38.5%) and Klebsiella spp. (37.9%) were more resistant to antibiotics tested.Conclusion: The higher number of drinking jar water in Kathmandu valley were contaminated with coliform and presence of biofilm forming antibiotic resistant enteric bacteria in water showed a high risk of waterborne infections to consumers. Quality control of drinking jar water is essential to improve water quality and prevent waterborne diseases.